Strong Convergence of Two-Dimensional Walsh–Fourier Series - Tephnadze, G. (Український математичний журнал, 2013)
We prove that certain means of quadratic partial sums of the two-dimensional Walsh–Fourier series are uniformly bounded operators acting from the Hardy space Hp to the space Lp for 0 < p < 1. Доведено, що певнi середнi квадратичних часткових сум двовимiрних рядiв Уолша – Фур’є є рiвномiрно обмеженими операторами, що дiють iз простору Хардi Hp у простiр Lp при 0< p <1.